Daphne jejudoensis Attenuates LPS-Induced Inflammation by Inhibiting TNF-α, IL-1β, IL-6, iNOS, and COX-2 Expression in Periodontal Ligament Cells - Ji-Yeong Bae; Dong-Seol Lee; You Kyoung Cho; Ji-Yeon Lee; Joo-Hwang Park; Sang Ho Lee (MDPI AG, 2022)
Periodontitis is a common disease involving inflammation and tissue destruction in the periodontal region. Although uncontrolled long-term inflammation in the gingiva may lead to loss of the periodontal ligament, treatments or preventive solutions for periodontitis are scarce. The aim of this study is to find anti-inflammatory material from a natural source that can be used to treat or protect against periodontitis. Daphne species (Thymelaeaceae) are important and popular components of traditional Chinese medicine and are used as anti-inflammatory agents. Daphne jejudoensis is an endemic plant that grows on Jeju Island and was identified as a new species in 2013. In this study, for the first time, we investigated the anti-inflammatory effect of D. jejudoensis leaf extract (DJLE) on human periodontal ligament cells. The gene expression levels of pro-inflammatory cytokines (interleukin-1β and 6 and tumor necrosis factor-α) and inflammation-inducible enzymes (inducible nitric oxide synthase and cyclooxygenase-2) were reduced after DJLE treatment with/without lipopolysaccharide stimulation. The findings of this study indicate that D. jejudoensis possesses anti-inflammatory activities, suggesting that DJLE may be a potential preventive and therapeutic agent for periodontitis.